2003
DOI: 10.2355/isijinternational.43.1219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intercritical Deformation on Bainite Formation in Al-containing TRIP Steel

Abstract: The Influence of intercritical deformation, cooling rate and prior austenite grain size on bainite formation were investigated by dilatometry tests. Intercritical deformation (0-40 %) performed in steels with a prior austenite grain size of 15-28 mm leads to formation of more ferrite during the cooling and less bainite during the subsequent isothermal stage, and even almost no bainite is formed after 40 % strain. Fast cooling after deformation can suppress ferrite transformation. Relaxation following deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…To convert the length change from the dilatometry measurement, D l/l 0 ,i nto the volume fraction change during phase transformations, many authors used alinear assumption between length and volume [33][34][35] ,w hich may be inaccurate for some cases. To improve this, the influence of chemical composition on lattice parameter is taken account, [26,36,37] which often requiresacomplicated numericalc alculation to solve the equations.…”
Section: Appendix Bmentioning
confidence: 99%
“…To convert the length change from the dilatometry measurement, D l/l 0 ,i nto the volume fraction change during phase transformations, many authors used alinear assumption between length and volume [33][34][35] ,w hich may be inaccurate for some cases. To improve this, the influence of chemical composition on lattice parameter is taken account, [26,36,37] which often requiresacomplicated numericalc alculation to solve the equations.…”
Section: Appendix Bmentioning
confidence: 99%
“…It has been proved that deformation varies temperature and time of the transformations during continuous cooling austenite (Jandova et al, 2002;Ming-Chun and Fu-Ren, 2003;Tamura et al, 1988). Other authors have demonstrated that the type of deformation (tensile, compression, hydrostatic or torsion) (Easterling and Porter, 1992;Bhadeshia, 1992), the amount of strain (Fang et al, 2003;Murr et al, 1982), strain rate (Murr et al, 1982;Luo et al, 2003) in thermomechanical process and prior austenite grain size (Luo et al, 2003) have distinct effects on martensite transformation (MT) and bainite transformation (BT). Also it has been proved that by strain, the nucleation sites of martensite and bainite increase (Murr et al, 1982;Pope, 1972;Nichol et al, 1977;Olson and Cohen, 1975;Koyima et al, 1996;Breedis, 1965).…”
Section: Introductionmentioning
confidence: 98%
“…Among various alloying elements that can substitute for Si, Al has been actively investigated [9,10], as it is known to suppress carbide formation in austenite. Al, however, has little solid-solution hardening effect in ferrite, and the substitution of Si with Al significantly reduces the alloy's strength.…”
Section: Introductionmentioning
confidence: 99%